2022
DOI: 10.3390/en15030914
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Series Self-Supervised Learning Approach to Detection of Cyber-physical Attacks in Water Distribution Systems

Abstract: Water Distribution System (WDS) threats have significantly grown following the Maroochy shire incident, as evidenced by proofed attacks on water premises. As a result, in addition to traditional solutions (e.g., data encryption and authentication), attack detection is being proposed in WDS to reduce disruption cases. The attack detection system must meet two critical requirements: high accuracy and near real-time detection. This drives us to propose a two-stage detection system that uses self-supervised and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Another problem that households have to face is frequent attacks on water supply facilities, because this way, water distribution systems (WDSs) are deregulated [221]. To address this problem, it is proposed that in addition to traditional solutions such as data encryption and authentication, it is proposed to detect attacks on WDSs to reduce the cases of disruption.…”
Section: Using ML For Water Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem that households have to face is frequent attacks on water supply facilities, because this way, water distribution systems (WDSs) are deregulated [221]. To address this problem, it is proposed that in addition to traditional solutions such as data encryption and authentication, it is proposed to detect attacks on WDSs to reduce the cases of disruption.…”
Section: Using ML For Water Activitiesmentioning
confidence: 99%
“…For high accuracy, heuristic adaptive self-predictive algorithms are applied for nearreal-time decision making and detection sensitivity. Unsupervised algorithms attempt to detect the attacks to maintain high detection accuracy as much as possible using isolation forest [221]. Based on the problems mentioned above, the World Health Organization has taken actions on water safety plans (WSPs), which involve holistic assessment and risk assessment.…”
Section: Using ML For Water Activitiesmentioning
confidence: 99%
“…Since the ultimate goal of pressure management is to reduce network leakage, studies often determine whether a DMA or a zone is necessary for pressure management based on the leakage rate. The minimum night flow method (MNF method) is often used as an important method for network leakage analysis, involving the determination of the minimum night flow and the determination of the legal water consumption of the customer at night, which can yield the night leakage of a DMA or a zone [12]. Cheung [13] through a study of Brazilian water consumption data, concluded that the MNF occurs between 1:00 a.m. and 4:00 a.m.…”
Section: Pressure-reducing Potentialmentioning
confidence: 99%
“…In addition, it is very cumbersome to repeat the design and build temporary pressure reduction stations for experiments at different locations. During the field experiment, intelligent pressure-regulating technology was born as a result of the widespread popularity of artificial intelligence [12] and supervisory control and data acquisition (SCADA) [13]. It can gather network operating data in real-time and realize pressure management without influencing customer water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to address regression-based challenges by producing predictions of stable or actual properties using aspects of easily available information. Surprisingly, the categorization totally isolates each item of data from the perspective of its class labels [22].…”
Section: Supervised Learningmentioning
confidence: 99%